Pengaruh Need for Achievement dan Innovativeness terhadap Entrepreneurial Intention yang dimediasi Entrepreneurial Attitude - Setiawan, Ainur Rahim; Murwani, F. Danardana; Kusumojanto, Djoko Dwi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Entrepreneurial Intention can be influenced by several factors, one of which is Need for Achievement, Innovativeness and Entrepreneurial Attitude. The purpose of this study was to determine how the influence of Need for Achievement, Innovativeness on Entrepreneurial Intention through Entrepreneurial Attitude. This research was conducted on students of the Faculty of Economics, majoring in Management, with a total sample of 227 students. This study uses the path analysis method. the results of this research, it shows that there is an influence of Need Need for Achievement, Innovativeness on Entrepreneurial Intention through Entrepreneurial Attitude.Abstrak: Minat berwirausaha dapat dipengaruhi oleh beberapa faktor, salah satunya faktor Need for Achievement, Innovativeness dan Entrepreneurial Attitude. Tujuan dalam penelitian ini untuk mengetahui bagaimana pengaruh Need for Achievement, Innovativeness terhadap Entrepreneurial Intention yang dimediasi Entrepreneurial Attitude. Penelitian ini dilaksanakan pada mahasiswa fakultas Ekonomi jurusan Manajemen yang memiliki jumlah sampel 227 mahasiswa. Penelitian ini menggunakan metode analisis jalur (Path Analysis). Dari hasil penelitian yang telah dilakukan menunjukkan bahwa terdapat pengaruh Need Need for Achievement, Innovativeness terhadap Entrepreneurial Intention yang dimediasi Entrepreneurial Attitude.